Factorize: y^3 - 1

### 3 Answers | Add Yours

we know a^3-b^3=(a-b)(a^2+b^2+ab)

here a=y and b=1 ,so we have

y^3-1=(y-1)(y^2+1+y)

To factorize `y^3 - 1` use the relation `a^3 - b^3 = (a - b)*(a^2 + ab + b^2)`

Substitute a^3 with y^3 and b^3 with 1 = 1^3. This gives:

y^3 - 1

= y^3 - 1^3

= (y - 1)(y^2 + y + 1)

**The factorized form of y^3 - 1 is (y - 1)(y^2 + y + 1)**

`y^3 - 1`

`(y-1)(y^2+y+1)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes